Treatment of Aneurysmal Bone Cysts with Bioactive Glass in Children. (March 2018) - Syvänen, J.; Nietosvaara, Y.; Kohonen, I.; Koskimies, E.; Haara, M.; Korhonen, J.; Pajulo, O.; Helenius, I.
Background and Aims: Aneurysmal bone cysts represent about 1% of primary bone tumors. The standard treatment is curettage, followed by local adjuvant treatments and bone grafting. The problem is the high recurrence rate. The purpose of this study was to evaluate retrospectively the use of bioactive glass as a filling material in the treatment of aneurysmatic bone cysts in children. Material and Methods: A total of 18 consecutive children (mean 11.3 years at surgery; 10 males; 11 lower, 6 upper limb, 1 pelvis; 15 with primary surgery) with histologically proven primary aneurysmal bone cysts operated with curettage and bioactive glass filling between 2008 and 2013 were evaluated after a mean follow-up of 2.0 years (range, 0.7–5.1 years). Results: Two (11%) patients showed evidence of aneurysmal bone cyst recurrence and both have been re-operated for recurrence. Bone remodeling was noted in all patients with remaining growth and no growth plate disturbances were recorded. Two patients needed allogeneic blood transfusion. No intraoperative or postoperative complications were recorded. Conclusion: We conclude that bioactive glass is a suitable filling material for children with primary aneurysmal bone cyst. Bioactive glass did not affect bone growth and no side effects were reported.